Delay contributing factors and strategies towards its minimization in IoT - Wan Abdul Rahman, Wan Fariza; Islam, Md Rafiqul; Hassan Abdalla Hashim, Aisha (Universiti Teknikal Malaysia Melaka, 2016)
nternet of Things (IoT) refers to various interconnected devices, typically supplied with limited computational and communication resources. Most of the devices are designed to operate with limited memory and processing capability, low bandwidth, short range and other characteristics of low cost hardware. The resulting networks are exposed to traffic loss and prone to other vulnerabilities. One of the major concerns is to ensure that the network communication among these deployed devices remains at required level of Quality of Service (QoS) of different IoT applications. The purpose of this paper is to highlight delay contributing factors in Low Power and Lossy Networks (LLNs) since providing low end- To-end delay is a crucial issue in IoT environment especially for mission critical applications. Various research efforts in relevance to this aspect are then presented.